METHODS OF THE FRACTAL APPROACH IN SCIENCE EDUCATION: INNOVATIVE TECHNOLOGY AND CONCEPTS OF COMPUTER MODELING - Yurkovych, Nataliya; Mar’yan, Mykhaylo; Opachko, Magdalena; Seben, Vladimir (Physical and Mathematical Education, 2023)
Formulation of the problem. At the present stage of the development of science education and information technology, their integration, complementarity, and implementation are essential. Therefore, the search for methods of teaching natural sciences, based on the principles of self-organization and computer modeling, corresponds to the immediate tasks of the present. Materials and methods. Methods of comparative analysis, computer modeling, and generalization strategy are used. The study is based on the physics course content and the use of the programming language. Results. An innovative fractal approach to the teaching of physical and mathematical disciplines is proposed as a method of improving independent and creative computer modeling of natural phenomena. The fundamental principles of object-oriented programming (encapsulation, inheritance, polymorphism) have proven to be influential in shaping the physical and mathematical aspects of the information architecture of the perception of educational disciplines. The possibility of using this approach in other sections of physics is demonstrated. The developed iterations of the fractal structure are presented in the example of the study of the "Geometric Optics" and "Wave Optics" sections of physics. It is shown that each iteration is characterized by synergy: the addition of a new iteration provides a high-quality and in-depth perception of new information. Conclusions. The formation of the specified integrated fractal structure conditions the integrity of information perception and its formation happens intuitively. The analysis of the conducted studies confirmed the innovativeness and effectiveness of the fractal approach. This approach can be used to develop systems for the processing and transmission of information, intelligent information materials, and artificial intelligence.